2013
DOI: 10.1016/j.bioelechem.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Direct electron transfer of Trametes hirsuta laccase adsorbed at unmodified nanoporous gold electrodes

Abstract: The enzyme Trametes hirsuta laccase undergoes direct electron transfer at unmodified nanoporous gold electrodes, displaying a current density of 28 A/cm 2 . The response indicates that ThLc was immobilised at the surface of the nanopores in a manner which promoted direct electron transfer, in contrast to the absence of a response at unmodified polycrystalline gold electrodes. The bioelectrocatalytic activity of ThLc modified nanoporous gold electrodes was strongly dependent on the presence of halide ions. Flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 44 publications
4
58
1
Order By: Relevance
“…An example of this was demonstrated by the Butt group in 2001, where NarGH NR (free of its NarI component) was studied at an electrode surface and NO Figure 11. Duca et al demonstrated the co-immobilization of NarGHI NR and Pt/Rh nanoparticles for the reduction of NO À 3 to NH 3 on a hybrid electrode, as reported in [50]. The 'Griess' assay was used to detect and quantify NO …”
Section: Inhibition Of Enzymatic Activitymentioning
confidence: 99%
“…An example of this was demonstrated by the Butt group in 2001, where NarGH NR (free of its NarI component) was studied at an electrode surface and NO Figure 11. Duca et al demonstrated the co-immobilization of NarGHI NR and Pt/Rh nanoparticles for the reduction of NO À 3 to NH 3 on a hybrid electrode, as reported in [50]. The 'Griess' assay was used to detect and quantify NO …”
Section: Inhibition Of Enzymatic Activitymentioning
confidence: 99%
“…This suggests that halides bind to the TNC center, with the biggest ions having restricted access to the trinuclear cluster. [65][66][67] An accurate mechanism and the precise binding site are, however, still being established, especially as a function of pH. [38,39] Furthermore, BODs are quite stable at neutral pH.…”
Section: Enzymes For O 2 Reductionmentioning
confidence: 99%
“…Trametes hirsute laccase (ThLc) showed well-defined DET at unmodified NPG electrodes, in 15 contrast to the absence of a response at unmodified polycrystalline gold electrodes [99]. [100].…”
Section: Multi-copper Oxidasesmentioning
confidence: 99%